ENHANCEMENT OF THE CURRICULUM UNIT PROGRAM FOR RESEARCH METHODS AND TECHNIQUES: METHODOLOGICAL SUGGESTIONS FOR EARLY CHILDHOOD EDUCATION TRAININ - Manuel Correia Filho, João; Roa Aleaga, Taimara (Revista Gênero e Interdisciplinaridade, 2025)
Currently, due to the complexity of Higher Education, there is a need for the participation of teachers who, faced with the practices and challenges of the subsystem, can develop teaching-learning environments that provide conditions for the formation of competent students, guiding them to learn in a coherent and contextualized manner. From this perspective, the curriculum and its different views allow for the structuring of the programs for the Curricular Units that are designed within it. Thus, the aim of the study was to critically and reflectively analyze the program of the Curricular Unit on Research Methods and Techniques, with a view to improving the teaching-learning process in the Bachelor’s degree in Early Childhood Education. Therefore, the research is situated within the interpretative paradigm using a qualitative approach, relying on documentary analysis of the program under study. The aim of this study is not to generalize the results but to interpret the phenomenon in context based on the existing theoretical references. The study allowed for an understanding of the need to improve the program of the curricular unit under study, as it will enable the teacher’s action to be more efficient in a coherent manner, so that the teaching-learning process delivered by the teacher achieves its intended objectives.